2008
DOI: 10.1007/s10815-008-9200-y
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of preimplantation genetic diagnosis for aneuploidy screening in repeated IVF-ET cycles among women with recurrent implantation failure

Abstract: Objective To determine the predictive value of euploid embryos in women with recurrent implantation failure undergoing repeated IVF-ET cycles with PGD (PGD). Design Cohort of IVF-PGD cycles in a tertiary care ART facility. Materials and method(s) Fifty-five consecutive patients with repeated implantation failure (more than three failed IVF-ET cycles) underwent two or more PGD cycles for aneuploidy testing. Mean maternal age was 37.6±5.3 years. Biopsies were performed on day 3. One blastomere was removed from e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 15 publications
1
28
0
Order By: Relevance
“…However, the results of our sensitivity analysis indicated that clinics with high (>25%) PGD rates did not have better treatment outcomes than clinics with lower rates. Although NASS collects information on the number of previous IVF cycles, it does not include information on previous PGD cycles or the availability of euploid embryos, particularly for two consecutive PGD cycles, which has been associated with improved pregnancy and implantation rates (25). Finally, as with any clinical diagnostic test, misdiagnosis of embryos can occur in PGD because of the technical difficulty of handling delicate cells and the fact that the cells can only be tested once; potential errors can occur and may result in the transfer of chromosomally abnormal or aneuploidy embryos (2, 19, 2527).…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of our sensitivity analysis indicated that clinics with high (>25%) PGD rates did not have better treatment outcomes than clinics with lower rates. Although NASS collects information on the number of previous IVF cycles, it does not include information on previous PGD cycles or the availability of euploid embryos, particularly for two consecutive PGD cycles, which has been associated with improved pregnancy and implantation rates (25). Finally, as with any clinical diagnostic test, misdiagnosis of embryos can occur in PGD because of the technical difficulty of handling delicate cells and the fact that the cells can only be tested once; potential errors can occur and may result in the transfer of chromosomally abnormal or aneuploidy embryos (2, 19, 2527).…”
Section: Discussionmentioning
confidence: 99%
“…A high incidence of complex chromosome abnormalities has been discovered in cleaving embryos from patients with RIF [49, 50]. …”
Section: Discussionmentioning
confidence: 99%
“…4,23,121,122,129,133,140,141 PGS for advanced maternal age, repeated pregnancy loss, repeated IVF failures, and severe male infertility was on the rise until 2007. 25,45,119,122,[142][143][144][145][146][147] So far RCTs have failed to demonstrate the suggested benefit of PGS for advanced maternal age in routine IVF/ICSI treatments when one to two blastomeres were biopsied on day 3 and were analyzed by fluorescent in situ hybridization. 23 New studies analyzing either polar bodies or blastocysts for 24 chromosomes are ongoing in Europe and the United States, and they may shed new light on the use of PGS.…”
Section: The Future Of Pgdmentioning
confidence: 99%